Maternal Care by the Earwig Doru lineare Eschs. (Dermaptera: Forficulidae) - Butnariu, Alessandra Regina; Pasini, Amarildo; Reis, Fernanda Santos; Bessa, Eduardo [UNESP] (Springer Nature, 2013)
We performed laboratory experiments to study maternal care in Doru lineare Eschs. (Dermaptera: Forficulidae), a predator of the maize pest Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae). Females laid 29.7 ± 8.43 (SD) eggs which took 7-10 days to hatch. Mothers searched for an appropriate nest, where they cleaned and defended eggs and nymphs. Females did not recognize eggs from other females as foreign and adopted them. Other evidence of maternal behavior was also observed, such as egg-cleaning, nest-cleaning, and a lower viability of eggs not cared for by females. © 2013 Springer Science+Business Media New York.
Keywords: adoption; behavior; Biological control; egg cleaning; predator; reproduction; Dermaptera; Doru lineare; Forficulidae; Lepidoptera; Noctuidae; Spodoptera frugiperda; Zea mays